SWRK-04. FAMILY HUDDLE – ONE FAMILY'S PERSONAL EXPERIENCE. Issue 2 (22nd June 2018) - Fernandez, Kate; Cameron, Kate
Abstract: The Family Huddle Framework was developed in 2016 to facilitate consumer engagement in the Women's and Children's Health Network (WCHN) care settings. It aims to understand what the consumer believes to be important to enhancing quality, comfort and safety of care provided on inpatient wards. The Family Huddle was piloted in early 2016 in a Medical/Surgical babies ward (birth to 1 year) and subsequently implemented and evaluated in the Michael Rice Centre for Haematology and Oncology (MRCHO) from October 2016. Parent/Caregiver consumers are invited to a regular (three weekly), semi-formal group meeting with a staff member to exchange information and ideas. The purpose is to improve care through sharing information, providing feedback, informing consumers of upcoming events, and giving opportunity for direct input on issues relevant to the area. In the MRCHO there have been ten huddles held with an average of five parents per meeting. Key outcomes that have been able to be addressed from the huddles include much improved internet access across the ward area, more comfortable seating in the waiting area and an increase in the variety of hospital food for inpatients. The impact this meeting had on a family whose child had been diagnosed with a central nervous system tumour will be explored in a case study.